Frontline Science: Kindlin‐3 is essential for patrolling and phagocytosis functions of nonclassical monocytes during metastatic cancer surveillance. Issue 6 (9th May 2020) - Marcovecchio, Paola M.; Zhu, Yanfang Peipei; Hanna, Richard N.; Dinh, Huy Q.; Tacke, Robert; Wu, Runpei; McArdle, Sara; Reynolds, Sophia; Araujo, Daniel J.; Ley, Klaus; Hedrick, Catherine C.
Abstract: Nonclassical monocytes maintain vascular homeostasis by patrolling the vascular endothelium, responding to inflammatory signals, and scavenging cellular debris. Nonclassical monocytes also prevent metastatic tumor cells from seeding new tissues, but whether the patrolling function of nonclassical monocytes is required for this process is unknown. To answer this question, we utilized an inducible‐knockout mouse that exhibits loss of the integrin‐adaptor protein Kindlin‐3 specifically in nonclassical monocytes. We show that Kindlin‐3‐deficient nonclassical monocytes are unable to patrol the vascular endothelium in either the lungs or periphery. We also find that Kindlin‐3‐deficient nonclassical monocytes cannot firmly adhere to, and instead "slip" along, the vascular endothelium. Loss of patrolling activity by nonclassical monocytes was phenocopied by ablation of LFA‐1, an integrin‐binding partner of Kindlin‐3. When B16F10 murine melanoma tumor cells were introduced into Kindlin‐3‐deficient mice, nonclassical monocytes showed defective patrolling towards tumor cells and failure to ingest tumor particles in vivo . Consequently, we observed a significant, 4‐fold increase in lung tumor metastases in mice possessing Kindlin‐3‐deficient nonclassical monocytes. Thus, we conclude that the patrolling function of nonclassical monocytes is mediated by Kindlin‐3 and essential for these cells to maintain vascular endothelial homeostasis and prevent tumor metastasis to the lung. Abstract : Study shows that loss of Kindlin‐3 in nonclassical monocytes reduces their ability to move toward and uptake tumor particles and perturbs endothelial homeostasis.